2020
DOI: 10.3389/fpsyt.2020.582189
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Anxiety, Fear, and Psychological Distress About COVID-19 Among University Students in the United Arab Emirates

Abstract: Background: Fear of infection, the epidemic situation, unexpected lockdown, and implementation of online classes are most likely affecting the psychological well-being of students during the COVID-19 pandemic. Therefore, this study aims to assess the level of knowledge, anxiety, and psychological distress concerning COVID-19 and their association with fear, gender, age, history of mental illness, time spent reading about COVID-19, program of study, and type of dwelling among students in the United Arab Emirate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
95
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 33 publications
(55 reference statements)
16
95
2
2
Order By: Relevance
“…This hypothesis could be supported by the aforementioned study conducted by Saravanan et al 16 and the “infodemic”. There are also researches conducted upon physicians.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This hypothesis could be supported by the aforementioned study conducted by Saravanan et al 16 and the “infodemic”. There are also researches conducted upon physicians.…”
Section: Discussionmentioning
confidence: 54%
“…Sahu et al 15 referred to the problem as an “infodemic” and pointed out that the evergrowing usage of social media platforms are amplifying the problem. A study by Saravanan et al 16 stated students who exhibited anxiety concerning COVID-19 anxiety and fear, and who spent more than 4 hours reading about COVID-19 were more psychologically distressed. Above all, people who were diagnosed with obsessive-compulsive disorder, borderline personality disorder, and narcissistic personality disorder may experience severe anxiety, fear, helplessness, desperation, hopelessness, feeling of worthlessness, and even psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…During COVID-19 pandemic, there were substantial increases in the levels of anxiety and depression, substance use, loneliness, domestic violence, and child abuse and maltreatment (Galea et al, 2020). A number of studies examined the impact of COVID-19 on mental health of population of Arab as well as the prevalence of mental health problems (Saravanan et al, 2020). Alkhamees et al (2020) reported that nearly 24% of general population of Saudi Arabia reported moderate or severe psychological impact of the outbreak with 28.3%, 24%, and 22.3% of the population respectively reported moderate to severe depressive, anxiety, and stress symptoms.…”
mentioning
confidence: 99%
“…Lukács ( 2021 ) evidenced that university students experienced significant negative changes after the first month of isolation regarding physical activity, relationship with family and friends, financial situation, perceived health, and perspective for the future. Morever, age, housing conditions, previous history of mental issues, anxiety, and fear significantly predicted psychological distress (Saravanan et al, 2020 ). Moreover, stress related to academics (e.g., personal uncertainties about academic program, distance teaching), health, and lack of social support predicted more negative mental health impacts (Lai et al, 2020 ).…”
mentioning
confidence: 99%